KONTEKSTUALISASI DAN HARMONISASI KESETARAAN GENDER DALAM REALITAS SOSIAL - M. Zaki (UIN Mataram, 2018)
The issue of men and women is very interesting when connected with Islamic discourse, which is indeed one component in various social, cultural and even political changes. Various efforts have been made to develop these issues starting from the deconstruction of the Islamic treasure to its reconstruction efforts. One of the subjects of study is the problem of male and female relations. In the context of these relations, men are always perceived as having a public role area and women are considered as the rulers and determinants of domestic roles. Therefore, both are assumed to have different areas of self-actualization.This cultural barrier, according to feminists, is a cultural and cultural heritage both from primitive society, agrarian society, and modern society. On the other hand a lot of understanding of the text was found to strengthen and even contribute to perpetuating the construction of the culture, which notes that the texts were derived from patriarchal Arabic culture, so that the interpretation is always gender-biased. Whereas in different approaches there are many texts which actually support the equality of relations between men and women.